Vitamin D Receptor FokI, ApaI, and TaqI Polymorphisms in Lead Exposed Subjects From Saudi Arabia - Shaik, Abjal Pasha; Alsaeed, Abbas H.; Faiyaz-ul-Haque, M.; Alsaeed, Mikqdad A.; Alyousef, Abdullah A.; Bammidi, Vamsee K.; Shaik, Asma Sultana (Frontiers in Genetics, 2019)
Vitamin D receptor (VDR) gene polymorphisms were reported to influence blood lead levels (BLL) and the response of subjects to the symptoms of lead toxicity. However, no studies have been conducted in the Saudi Arabian population which has unique ethnicity and socio-demographic features. This study was therefore conducted to examine the polymorphisms in exon 2 (allele 1) and intron 8 (allele 2 and allele 3) of VDR gene and their relation to BLLs. As per the CDC guidelines, the recruited lead-exposed workers (N=130) were categorized to two groups viz., low BLL group (<10 μg/dL) and high BLL group (>10 μg/dL). The low BLL group had a mean level of 4.37 µg/dL, while the high BLL group had levels of 18.12 µg/dL (p<0.001). Overall, the genetic variants, TC and CC in the VDR FokI were significantly associated with a risk of lead toxicity and the allele ‘C’ was a risk factor (p=0.00026). Furthermore, the TT genotype of VDR ApaI significantly increased the risk of developing lead poisoning (p=0.0006). The VDR TaqI SNP was not significantly associated with lead toxicity. The highest BLLs for VDR FokI-CC, VDR ApaI-GG and VDR TaqI-TT genotypes from High BLL group were 18.42, 15.26 and 18.75 μg/dL, respectively. Older age (51-60 years) was found to be a significant confounding factor for BLLs (p=0.012). Additional studies in larger sample sizes are needed to firmly establish the role of VDR genotypes and genetic susceptibility to lead poisoning.